Effect of Synbiotics Supplementation in Feed on Tegal Male Duckâs Internal Organs - Iriyanti, Ning; Hartoyo, Bambang (Universitas Jenderal Soedirman, Faculty of Animal Science, Purwokerto-Indonesia, 2017)
The aim of this research was to review the application of synbiotics in duck feed towards its gastrointestinal and internal organsâ effectivity. The study was carried out to 60 two-months old drake. The feed given to the research subjects consisted of soybean meal, fishmeal, methionine, lysine (PT. CJeil Jedang Tbk. Indonesia), corn, bran, oil, premix, CaCO3 and synbiotics (Lactobacillus sp. and inulin prebiotics). The ratio of feed was based on isoprotein and isocalorie, with 19% of protein and 2900 kcal/kg of metabolic energy. The research was under a fully randomized in vivo experimental method with 4 treatments and 5 replicates, using 3 drakes each. These treatments were R0: controlled feed, with 0% of synbiotics; R1: feed with 2% of synbiotics; R2: feed with 4% of synbiotics; and R3: feed with 6% of synbiotics. Data obtained were subject to analysis of variance. The results show that the use of synbiotics in feed does not have any significance on the weight and length of duodenum, jejunum, and ileum. It also does not have any significance on the weight of gall, pancreas, gizzard, liver and heart. In conclusion, feed with 6% or less of synbiotics can be used without affecting the physical condition of gastrointestinal (weight and length) and internal organ (weight)